1995
DOI: 10.1084/jem.181.6.2129
|View full text |Cite
|
Sign up to set email alerts
|

Transitional B cells are the target of negative selection in the B cell compartment.

Abstract: SummaryB lymphocytes recognize antigen through membrane-bound antigen-receptors, membrane IgM and IgD (mlgM and mlgD). Binding to foreign antigens initiates a cascade of biochemical events that lead to activation and differentiation. In contrast, binding to self-antigens leads to death or to inactivation. It is commonly believed that the B cells acquire the ability to discriminate between self and nonself in the early phases of development. We report here that immature B cells, which have just emerged from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
265
2
2

Year Published

1998
1998
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(278 citation statements)
references
References 48 publications
9
265
2
2
Order By: Relevance
“…Several studies have suggested that exposure to Ag deletes newly generated B cells more readily than mature B cells (37)(38)(39)(40); however, previous studies with Ig Tgn and HEL-Ig mice and with mice injected with anti-IgD mAb have demonstrated that mIg crosslinking in the absence of T cell help also deletes mature B cells (12,32,41). Our studies with IL-4 suggest that the difference between the behavior of immature and mature B cells is quantitative rather than qualitative.…”
Section: Relationship Between B Cell Survival and Maturitymentioning
confidence: 50%
“…Several studies have suggested that exposure to Ag deletes newly generated B cells more readily than mature B cells (37)(38)(39)(40); however, previous studies with Ig Tgn and HEL-Ig mice and with mice injected with anti-IgD mAb have demonstrated that mIg crosslinking in the absence of T cell help also deletes mature B cells (12,32,41). Our studies with IL-4 suggest that the difference between the behavior of immature and mature B cells is quantitative rather than qualitative.…”
Section: Relationship Between B Cell Survival and Maturitymentioning
confidence: 50%
“…The comparatively modest increase in Ccnd2 and Plk expression could reflect heterogeneity in the splenic B cell population; although most splenic B cells are mature follicular cells, they also include transitional immature cells and mature marginal zone cells (39,40). It is known that immature B cells undergo apoptosis and down-regulate Ccnd2 in response to anti-Ig (39,41,42), but do proliferate to the other mitogen, LPS (39). It is possible that different gene response patterns to anti-Ig in the B cell subsets could dilute or cancel each other out at the population level, contributing to less up-regulation of Ccnd2 and Plk.…”
Section: Gene Expression Change Patterns Distinguishing Anti-igmentioning
confidence: 99%
“…Here we show that ⌬V cells have a phenotype consistent with the idea that the mutant BCR has enhanced constitutive activity. ⌬V cells are functionally similar to tolerized B cells and are eliminated at the transitional B cell stage (18), cells with lower levels of receptors being spared. We also show that the truncated BCR allows the exit in periphery of cells with a very immature phenotype.…”
mentioning
confidence: 99%